Penerapan Metode Modified K-Nearest Neighbor pada Klasifikasi Penyakit Menular Seksual Pria - Yoseansi Mantharora Siahaan; Imam Cholissodin; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Sexually transmitted diseasse are a type of disease that spreads quite quickly. According to a World Health Organization (WHO) report, cases of infection that spread through sexual contact can be found every day with sexually active populations, namely adults and adolescents, especially men. The similarity in symptoms for each disease and patients are generally less familiar with the initial symptoms so they cannot provide early help. By developing the Modified K-Nearest Neighbor algorithm and using the asymmetric binary distance, the test result obtained on the effect of the K values of 100% in the 9th test. The K-Fold = 10 gets 91,67% results by using K = 9. And the Precision value = 1for Gonorrhea and HIV classes, and Recall value = 1 for the Warts and HIV classes.